A Rare Case of Sudden Cardiac Death - Alhad Mulkalwar; T Jadhav; J Savla; P Vaideeswar (Tropical Journal of Pathology and Microbiology, 2022)
- While sudden deaths fall within the purview of forensic experts, they are often found to be causedby cardiovascular pathologies (to the extent of 85%), which may be evident or occult [1]. A suddencardiac death is an unexpected death owing to a cardiac cause which generally occurs within an hourof onset of symptoms [2, 3]. Most sudden cardiac deaths are due to coronary artery diseases [4, 5].The remainder is caused by a heterogeneous group of non-ischemic disorders, most of which resultin structural cardiac abnormalities [6]. Herein we describe, at autopsy, a case of a sudden cardiacdeath secondary to an arrhythmogenic cardiomyopathy